Exploring nurse-led cystoscopy: A systematic review of safety, efficacy, and applicability in urogynecology - Aditi Siddharth; Nadia Muspratt Tucker; Rufus Cartwright (Journal of Current Research in Scientific Medicine)
Cystoscopy is traditionally performed by doctors with specialist training. Increasing demand and workforce challenges have led to prolonged wait times for cystoscopy. Nurse-led clinics have been successful in many medical fields, but their widespread adoption for cystoscopy remains limited in urogynecology. The systematic review aimed to assess the effectiveness of nurse-led cystoscopy clinics, focusing on safety, acceptability, and service impact. A search was performed in Medline, EMBASE, CINAHL, and conference abstracts using MeSH terms, until February 2021. Study selection and data extraction were performed independently by two reviewers with a third acting as arbitrator. Narrative synthesis was used to report the findings due to the heterogeneity of the studies. The review included 25 urology studies with most addressing bladder cancer surveillance. Nurse-led cystoscopy clinics were found to be as safe and effective as consultant-led clinics, with comparable diagnostic yield and cancer detection rates. Adverse outcomes were rare. Patients and staff showed high levels of acceptability, with patients reporting better experiences and timely appointments. Nurse-led clinics significantly reduced wait times and improved continuity of care for follow-up cystoscopies. Nurse-led cystoscopy clinics offer a potential solution to address the challenges faced by urogynecology departments. These clinics are safe, effective, and well accepted by patients and staff and well established in urology. Successful implementation requires commitment from management and the multidisciplinary team, along with the establishment of protocols and regular audits. Further research and randomized controlled trials are needed to strengthen the evidence in this field.